Theoretical Concepts used in building Cyber Resilience - Claudiu-Cosmin RADU (Bulletin of "Carol I" National Defense University)
In the context of intensifying cyber threats, cyberspace resilience has become a strategic priority for organizations, governments, and international alliances. Cyber scenarios, in their various forms, provide a controlled environment in which response capabilities to cybersecurity incidents can be tested, trained, and validated. The aim of this paper is to analyze how these scenarios contribute to the development of an organizational culture of resilience, allowing the identification of vulnerabilities, strengthening decision-making under pressure, and proactively adapting to new types of threats. The study explores current practices adopted at the European and international level, revealing how scenario-based exercises support strategic planning, training of technical and operational teams, and interinstitutional cooperation. Moreover, the direct benefits to organizational flexibility and post-incident recovery capacity are also analyzed. Finally, the article formulates a series of recommendations for integrating scenarios into the cyber risk management cycle, highlighting their value not only as training tools but also as fundamental elements in the security architecture of a modern organization.